Preparation method of self-repairing waterborne polyurethane coating based on synergistic effect of dynamic disulfide bond and pH response microcapsule

Through the self-healing aqueous polyurethane coating that synergizes dynamic disulfide bonds and pH-responsive microcapsules, the problem of traditional self-healing coatings being easily damaged under mechanical impact is solved, and the rapid low-temperature repair and long-term anti-corrosion are achieved, which is suitable for environments such as automobiles and marine equipment.

CN120399557APending Publication Date: 2025-08-01SHAANXI COALFIELD GEOLOGY GRP CO LTD +1
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202510853331.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-24
Publication Date
2025-08-01

AI Technical Summary

Technical Problem

The existing self-repair coatings are prone to micron-scale cracks under mechanical impact or fatigue loads, resulting in corrosive media penetration. The traditional microcapsule type repair effect is limited, and the intrinsic self-repair material is high in energy consumption, difficult to adapt to low-temperature working conditions, and lacks active corrosion inhibition function.

Method used

A self-healing aqueous polyurethane coating with dynamic disulfide bonds and pH-responsive microcapsules was used to synergize the self-healing coating by preparing a dynamic disulfide bond-containing aqueous polyurethane emulsion and pH-responsive microcapsules, combined with TEMPO oxidized nanocellulose, a self-healing coating was constructed, and the thiol catalyst was used to synergize the thiol group of cysteine and reduce the repair temperature and enhance the cohesion and toughness of the coating.

Benefits of technology

It realizes rapid low-temperature repair, mechanical strength recovery rate ≥90%, extends the response time of microcapsules, provides long-term anti-corrosion performance, and is suitable for harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120399557A_ABST
    Figure CN120399557A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a self-repairing waterborne polyurethane coating based on a synergistic effect of a dynamic disulfide bond and a pH response microcapsule. The preparation method comprises the following steps: step 1, preparing a dynamic disulfide bond-containing waterborne polyurethane (D-WPU) emulsion; step 2, preparing a pH response microcapsule; step 3, preparing a self-repairing waterborne polyurethane coating; a dynamic disulfide bond of the self-repairing waterborne polyurethane coating rapidly repairs macrocracks at 50-60 DEG C through mercaptan catalysis, and pH < lt > is caused by local corrosion of a pH response microcapsule; when the pH value is 4.0, cysteine is released, sulfydryl accelerates recombination of dynamic bonds, and amino enhances cohesive force of the coating and neutralizes H < + >. And in combination with a hydrogen bond network of the nanocellulose, the coating has low-temperature repair (the mechanical strength recovery rate is greater than or equal to 90%), high toughness (the water absorption rate is less than or equal to 2.1%) and long-acting corrosion resistance (the salt spray resistance life is greater than or equal to 600 hours), and is suitable for severe environments such as ocean engineering and new energy equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of metal surface anti-corrosion coatings, and specifically relates to a preparation method of a self-healing waterborne polyurethane coating based on the synergistic effect of dynamic disulfide bonds and pH-responsive microcapsules. Background Art

[0002] With the acceleration of the global industrialization process, metal corrosion, as a form of material failure, is posing a severe challenge to strategic industries such as new energy equipment, ocean engineering, and rail transit. Although traditional protective coatings can provide a basic barrier function, under complex working conditions, the local corrosion diffusion caused by coating damage often leads to the premature failure of structural components, seriously affecting the service safety of equipment and the efficiency of resource recycling. Traditional anti-corrosion coatings rely on physical barrier effects, but materials are prone to micron-sized cracks under working conditions such as mechanical impact and fatigue load, resulting in the rapid penetration of corrosive media along the defects and triggering local pitting diffusion, greatly reducing the anti-corrosion performance of the coatings.

[0003] Self-healing coatings are an effective strategy to solve this problem, but existing self-healing technologies have limitations. Although microcapsule-based repair systems can release corrosion inhibitors, their repair effect is limited when scratches or cracks are generated on the coating surface due to external forces, and long-term protection cannot be achieved after a single release; although intrinsic self-healing materials can achieve bulk repair, they have high energy consumption and are difficult to adapt to low-temperature working conditions; in addition, they lack an active corrosion inhibition function and cannot inhibit secondary damage caused by the penetration of corrosive media. Constructing a dual mechanism of dynamic bond repair matrix and microcapsule fixed-point corrosion inhibition can solve the limitations of a single anti-corrosion mechanism, but it is difficult to effectively reduce the self-healing temperature of intrinsic self-healing materials based on dynamic disulfide bonds, and traditional microcapsule core materials often have a complex composition and are not environmentally friendly. Cysteine is a natural amino acid with good biocompatibility and easy degradation, meeting the requirements of green chemical engineering. Moreover, the sulfhydryl group and amino group of cysteine are respectively targeted at dynamic bond repair and coating strengthening, and a "repair-corrosion inhibition-enhancement" trinity mechanism can be achieved. Summary of the Invention

[0004] In order to solve the defects of existing self-healing coatings, the present invention provides a preparation method of a self-healing waterborne polyurethane coating based on the synergistic effect of dynamic disulfide bonds and pH-responsive microcapsules.

[0005] To this end, the present invention provides a preparation method of a self-healing waterborne polyurethane coating based on the synergistic effect of dynamic disulfide bonds and pH-responsive microcapsules, including the following steps: Step 1, prepare a waterborne polyurethane (D-WPU) emulsion containing dynamic disulfide bonds; Step 2, prepare pH-responsive microcapsules; Step 3, prepare a self-healing waterborne polyurethane coating.

[0006] Further, the specific process of Step 1, preparing the aqueous polyurethane (D-WPU) emulsion containing dynamic disulfide bonds, is as follows: Mix polytetrahydrofuran diol (PTMG, Mn = 2000), isophorone diisocyanate (IPDI), and 2,2-dimethylolpropionic acid (DMPA, carboxyl content 5%) in a ratio of 2:1 in terms of the molar ratio of NCO groups to hydroxyl groups (OH), react at 80 °C for 3 hours to obtain an NCO-group-terminated prepolymer. Cool the prepolymer to 60 °C, add cystamine hydrochloride (—NCO:NH2 = 1:0.6) and a thiol catalyst, react for 4 hours under nitrogen protection, add deionized water for emulsification (solid content 40%), and adjust the pH to 7.0 ± 0.5 to obtain the D-WPU emulsion containing dynamic disulfide bonds.

[0007] Further, the specific steps of Step 2, preparing pH-responsive microcapsules, are as follows: Step 201, preparation of the core material solution: Weigh 10.0 g of cysteine, add 90.0 mL of phosphate buffer solution (pH = 4.0), stir magnetically for 30 min until completely dissolved, and ultrasonically disperse until the solution is clear to avoid particle residue; Step 202, preparation of the wall material solution: Weigh 1.0 g of dopamine hydrochloride, dissolve it in 99.0 mL of Tris-HCl buffer solution (pH = 8.5), stir magnetically at 40 °C for 24 h to fully oxidize and polymerize dopamine into polydopamine (PDA), filter to remove unreacted monomers, and obtain a uniform PDA solution; Step 203, preparation of microcapsules: Use a coaxial microfluidic device to prepare microcapsules, control the flow rate ratio of the core material solution to the wall material solution to be 1:5, and directly collect the emulsion at the microfluidic outlet into a centrifuge tube to form monodisperse microcapsules; Step 204, centrifugal purification: Centrifugal speed: 3000 rpm, time: 10 minutes; remove the supernatant; Step 205, washing: Add deionized water and vortex to mix evenly; repeat the centrifugation (3000 rpm, 5 minutes) and supernatant removal steps 3 times to thoroughly remove impurities; Step 206, freeze-drying: Pre-freezing: Place the washed microcapsule suspension in a -30 °C refrigerator and freeze for 24 hours; drying: Transfer to a freeze-dryer (-50 °C, 0.1 mbar) and dry for 24 hours to obtain dry microcapsule powder.

[0008] Further, the inner tube of the coaxial microfluidic device is used as the core material channel and is a quartz capillary with an inner diameter of 0.5 mm and an outer diameter of 0.7 mm. The outer tube is used as the wall material channel and is a stainless steel sleeve with an inner diameter of 1.5 mm and an outer diameter of 2.0 mm. The distance between the inner and outer tubes is adjusted to 0.4 mm by a precision fixture, and the core material flow rate is controlled at 0.2 mL / min and the wall material flow rate is 1.0 mL / min.

[0009] Further, the specific process of step 3, preparing the self-healing aqueous polyurethane coating, is as follows: Stir the D-WPU emulsion, microcapsules (8 wt%), TEMPO-oxidized nanofibrillated cellulose (CNF, 1 wt%), and defoamer (0.5 wt%) at a low speed (500 rpm, 30 minutes); spray it onto the pretreated Q235 steel plate, and pre-cure it at room temperature for 24 hours, then gradually increase the temperature: cure at 60 °C for 2 hours and at 80 °C for 1 hour.

[0010] Further, the pretreatment process of the Q235 steel plate is as follows: polish the surface of the Q235 carbon steel plate with sandpaper, then clean its surface with a metal cleaner, and finally rinse the surface with clean water.

[0011] Further, the thiol catalyst is 1-octanethiol, and the addition amount is 0.5 wt% of the total mass of the prepolymer.

[0012] Further, the self-healing aqueous polyurethane coating can achieve scratch repair by heating at 50-60 °C for 1-1.5 h, and the mechanical strength recovery rate is ≥90%.

[0013] Further, the polydopamine shell layer of the pH-responsive microcapsules degrades at pH < 4.0, releasing cysteine. Its mercapto group (-SH) catalyzes the recombination of dynamic disulfide bonds, and after the amino group (-NH2) is protonated, it forms an ionic bond with the carboxyl group of the polyurethane, improving the mechanical strength of the self-healing aqueous polyurethane coating.

[0014] The advantages of the present invention are as follows: The present invention provides a preparation method of a self-healing waterborne polyurethane coating based on the synergistic effect of dynamic disulfide bonds and pH-responsive microcapsules. The sulfhydryl group (-SH) in cysteine and the thiol catalyst act synergistically to significantly reduce the activation energy of dynamic disulfide bond recombination, lower the repair temperature, and shorten the repair time. The amino group of cysteine will be protonated in an acidic environment, forming an ionic bond with the carboxyl group of the polyurethane matrix, enhancing the cohesion of the coating, increasing the tensile strength, neutralizing the H+ generated by local corrosion at the same time, delaying the pH decline rate, extending the response time of the microcapsules, and realizing the "repair-corrosion inhibition-strengthening" trinity mechanism; TEMPO-oxidized nanocellulose (CNF) forms a hydrogen bond network with the carboxyl group of the polyurethane through hydroxyl groups, improving the toughness of the coating and assisting stress transfer. Its three-dimensional network structure reduces the water absorption rate of the coating, enhances the water resistance, and at the same time acts as a physical barrier to delay the penetration of corrosive media.

[0015] A preparation method of a self-healing waterborne polyurethane coating based on the synergistic effect of dynamic disulfide bonds and pH-responsive microcapsules constructs an efficient self-healing waterborne polyurethane coating through dynamic chemical bond design, intelligent microcapsule structure optimization, and nano-enhancement synergy. It has low-temperature repair, high mechanical strength, and long-term anti-corrosion performance, and is suitable for harsh environments such as automobiles and marine equipment.

[0016] The following will describe the present invention in detail with reference to the accompanying drawings and embodiments. Description of the Drawings

[0017] Figure 1 It is a schematic diagram of the prepolymer synthesis of the present invention.

[0018] Figure 2 It is a water absorption rate curve graph of the coatings prepared in Example 1, Example 2, and Example 3 of the present invention.

[0019] Figure 3 It is a scratch repair rate curve graph of the coatings prepared in Example 1, Example 2, and Example 3 of the present invention. Detailed Embodiments

[0020] To further elaborate on the technical means and effects adopted by the present invention to achieve the predetermined purpose, the following will describe in detail the specific embodiments, structural features, and their effects of the present invention with reference to the accompanying drawings and embodiments.

[0021] The following will clearly and completely describe the technical solutions in the embodiments of the present invention with reference to the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention.

[0022] All features disclosed in this specification, or steps in all methods or processes disclosed, except for mutually exclusive features and / or steps, can be combined in any manner.

[0023] Any feature disclosed in this specification (including any additional claims, abstract, and drawings), unless specifically stated, can be replaced by other equivalent or similar-purpose alternative features. That is, unless specifically stated, each feature is just an example in a series of equivalent or similar features.

[0024] Example 1

[0025] To solve the defects of existing self-healing coatings, the present invention provides a method for preparing a self-healing aqueous polyurethane coating based on the synergistic effect of dynamic disulfide bonds and pH-responsive microcapsules.

[0026] This example provides a method for preparing a self-healing aqueous polyurethane coating based on the synergistic effect of dynamic disulfide bonds and pH-responsive microcapsules. The dynamic disulfide bonds repair macroscopic cracks. Cystamine hydrochloride (containing disulfide bonds S-S) is introduced into the polyurethane matrix, and its amino group (-NH2) reacts with the isocyanate group (-NCO) of the prepolymer to form a dynamic crosslinked network. The thiol catalyst (1-octanethiol) catalyzes the reversible reaction, which reduces the activation energy of the dynamic bond recombination and enables the rapid breaking and recombination of disulfide bonds. When the coating is damaged, local heating activates the thiol catalysis, and the dynamic bond recombination closes the cracks and restores the mechanical strength; the pH-responsive microcapsules inhibit local corrosion while reducing the repair temperature of the disulfide bonds. When the coating is damaged and corrosive media (such as H + ) invade, the local pH drops to acidic (pH < 4.0), the polydopamine shell dissolves, and the microcapsules rupture to release cysteine. The sulfhydryl group (-SH) of cysteine and the thiol catalyst (1-octanethiol) act synergistically to significantly reduce the activation energy of the dynamic chemical bond recombination through the thiol-disulfide exchange reaction, thereby reducing the repair temperature. At the same time, in the acidic corrosion environment, the amino group will be protonated, forming strong ionic bonds with the carboxyl groups of the polyurethane matrix, enhancing the cohesion of the coating, and the protonation of the amino group can neutralize the H + generated by local corrosion, delay the rate of pH drop, extend the response time of the microcapsules, and achieve a more lasting corrosion inhibition effect.

[0027] Specifically, a method for preparing a self-healing aqueous polyurethane coating based on the synergistic effect of dynamic disulfide bonds and pH-responsive microcapsules includes the following steps: Step 1, prepare an aqueous polyurethane (D-WPU) emulsion containing dynamic disulfide bonds; Step 2, prepare pH-responsive microcapsules; Step 3, prepare a self-healing aqueous polyurethane coating.

[0028] Further, the specific process of Step 1, preparing the aqueous polyurethane (D-WPU) emulsion containing dynamic disulfide bonds, is as follows: Mix polytetrahydrofuran diol (PTMG, Mn = 2000), isophorone diisocyanate (IPDI), and 2,2-dimethylolpropionic acid (DMPA, carboxyl content 5%) in a ratio of 2:1 in terms of the molar ratio of NCO groups to hydroxyl groups (OH). React at 80 °C for 3 hours to obtain an NCO-group-terminated prepolymer. Cool the prepolymer to 60 °C, add cystamine hydrochloride (—NCO:NH2 = 1:0.6) and a thiol catalyst, and react for 4 hours under nitrogen protection. Add deionized water for emulsification (solid content 40%), and adjust the pH to 7.0 ± 0.5 to obtain the D-WPU emulsion containing dynamic disulfide bonds.

[0029] Further, the specific steps of Step 2, preparing pH-responsive microcapsules, are as follows: Step 201, preparation of the core material solution: Weigh 10.0 g of cysteine, add 90.0 mL of phosphate buffer solution (pH = 4.0), stir magnetically for 30 min until completely dissolved, and ultrasonically disperse until the solution is clear to avoid particle residue; Step 202, preparation of the wall material solution: Weigh 1.0 g of dopamine hydrochloride, dissolve it in 99.0 mL of Tris-HCl buffer solution (pH = 8.5), stir magnetically at 40 °C for 24 h to fully oxidize and polymerize dopamine into polydopamine (PDA), filter to remove unreacted monomers, and obtain a uniform PDA solution; Step 203, preparation of microcapsules: Use a coaxial microfluidic device to prepare microcapsules, control the flow rate ratio of the core material solution to the wall material solution to be 1:5, and directly collect the emulsion at the microfluidic outlet into a centrifuge tube to form monodisperse microcapsules; Step 204, centrifugal purification: Centrifugal speed: 3000 rpm, time: 10 minutes; Remove the supernatant (unencapsulated core material and free wall material); Step 205, washing: Add deionized water (3 times the volume of the emulsion), vortex and mix well; Repeat the centrifugation (3000 rpm, 5 minutes) and supernatant removal steps 3 times to thoroughly remove impurities; Step 206, freeze-drying: Pre-freezing: Place the washed microcapsule suspension in a -30 °C refrigerator and freeze for 24 hours; Drying: Transfer to a freeze-dryer (-50 °C, 0.1 mbar) and dry for 24 hours to obtain dry microcapsule powder.

[0030] Furthermore, the inner tube of the coaxial microfluidic device serves as the core material channel and uses a quartz capillary with an inner diameter of 0.5 mm and an outer diameter of 0.7 mm. The outer tube serves as the wall material channel and uses a stainless steel sleeve with an inner diameter of 1.5 mm and an outer diameter of 2.0 mm. The distance between the inner and outer tubes is adjusted to 0.4 mm through a precision fixture to ensure stable laminar flow. The flow rate of the core material is controlled at 0.2 mL / min (precisely controlled by an injection pump), and the flow rate of the wall material is 1.0 mL / min.

[0031] Furthermore, the specific process of step 3, preparing the self-healing waterborne polyurethane coating, is as follows: Stir the D-WPU emulsion, microcapsules (8 wt%), TEMPO-oxidized nanocellulose (CNF, 1 wt%), and defoamer (0.5 wt%) at a low speed (500 rpm, 30 minutes); spray it onto the pretreated Q235 steel plate, and pre-cure it at room temperature for 24 hours (to volatilize water). Subsequently, raise the temperature in a gradient manner: cure at 60°C for 2 hours (to activate the thiol-catalyzed disulfide bond recombination), and cure at 80°C for 1 hour (for complete cross-linking).

[0032] Furthermore, the pretreatment process of the Q235 steel plate is as follows: polish the surface of the Q235 carbon steel plate with sandpaper, then clean its surface with a metal cleaner, and finally rinse the surface with clean water.

[0033] Furthermore, the thiol catalyst is 1-octanethiol, and the addition amount is 0.5 wt% of the total mass of the prepolymer.

[0034] Furthermore, the self-healing waterborne polyurethane coating can achieve scratch repair when heated at 50 - 60°C for 1 - 1.5 h, and the mechanical strength recovery rate is ≥90%.

[0035] Furthermore, the polydopamine shell layer of the pH-responsive microcapsules degrades at pH < 4.0, releasing cysteine. Its sulfhydryl group (-SH) catalyzes the recombination of dynamic disulfide bonds, and after the amino group (-NH2) is protonated, it forms an ionic bond with the carboxyl group of the polyurethane, enhancing the mechanical strength of the self-healing waterborne polyurethane coating.

[0036] In summary, for the preparation method of the self-healing waterborne polyurethane coating based on the synergistic effect of dynamic disulfide bonds and pH-responsive microcapsules, the thiol group (-SH) in cysteine and the thiol catalyst act synergistically to significantly reduce the activation energy of dynamic disulfide bond recombination, lower the repair temperature, and shorten the repair time. The amino group of cysteine will be protonated in an acidic environment, forming an ionic bond with the carboxyl group of the polyurethane matrix, enhancing the cohesion of the coating, increasing the tensile strength, neutralizing H⁺ generated by local corrosion at the same time, delaying the pH decline rate, prolonging the response time of the microcapsules, and realizing the "repair-corrosion inhibition-strengthening" trinity mechanism; TEMPO-oxidized nanocellulose (CNF) forms a hydrogen bond network with the carboxyl group of polyurethane through hydroxyl groups, improving the toughness of the coating and assisting stress transfer. Its three-dimensional network structure reduces the water absorption rate of the coating, enhances the water resistance, and at the same time acts as a physical barrier to delay the penetration of corrosive media.

[0037] For the preparation method of the self-healing waterborne polyurethane coating based on the synergistic effect of dynamic disulfide bonds and pH-responsive microcapsules, through the design of dynamic chemical bonds, the optimization of the intelligent microcapsule structure, and the synergistic effect of nano-enhancement, an efficient self-healing waterborne polyurethane coating has been constructed, which has low-temperature repair, high mechanical strength, and long-term anti-corrosion performance, and is suitable for harsh environments such as automobiles and marine equipment.

[0038] Example 2

[0039] A dynamic disulfide bond waterborne polyurethane coating based on a cystamine derivative, comprising the following steps: (1) Add 100.0 g of PTMG (0.05 moL), 44.4 g of IPDI (0.2 moL), and 13.3 g of DMPA (0.1 moL) to a three-necked flask, protect with nitrogen, and mechanically stir and react at 80 °C for 3 hours to obtain an -NCO-terminated prepolymer. Cool the prepolymer to 60 °C (cooling rate 5 °C / min), add 12.0 g of cystamine hydrochloride (molecular weight 225.7 g / moL) and 0.6 g of 1-octanethiol (0.5 wt%), stir and react for 4 hours under nitrogen protection, add 200.0 mL of deionized water for emulsification, and adjust the pH to 7.0 ± 0.5 by dropping triethylamine. After filtration, a D-WPU emulsion containing dynamic disulfide bonds (solid content 40%) is obtained.

[0040] (2) Spray 100.0 g of the D-WPU emulsion onto a Q235 steel plate (diameter 30 mm, thickness 0.5 mm) treated by sandblasting, pre-cure at room temperature for 24 hours (to volatilize water), and then raise the temperature gradient: cure at 60 °C for 2 hours and at 80 °C for 1 hour.

[0041] Example 3

[0042] A preparation method of a self-healing waterborne polyurethane coating based on the synergistic effect of dynamic disulfide bonds and pH-responsive microcapsules, comprising the following steps: (1) Add 100.0 g of PTMG (0.05 moL), 44.4 g of IPDI (0.2 moL) and 13.3 g of DMPA (0.1 moL) into a three-necked flask, protect it with nitrogen, and stir mechanically at 80 °C for 3 hours to obtain an -NCO-terminated prepolymer. Cool the prepolymer to 60 °C (cooling rate: 5 °C / min), add 12.0 g of cystamine hydrochloride (molecular weight: 225.7 g / moL) and 0.6 g of 1-octanethiol (0.5 wt%), stir and react for 4 hours under nitrogen protection, add 200.0 mL of deionized water for emulsification, and adjust the pH to 7.0 ± 0.5 by dropping triethylamine. After filtration, a D-WPU emulsion containing dynamic disulfide bonds (solid content: 40%) is obtained.

[0043] (2) Preparation of pH-responsive microcapsules: Preparation of core material solution: Weigh 10.0 g of cysteine, add 90.0 mL of phosphate buffer solution (pH = 4.0), stir magnetically for 30 min until completely dissolved, and ultrasonically disperse until the solution is clear to avoid particle residues. Preparation of wall material solution: Weigh 1.0 g of dopamine hydrochloride, dissolve it in 99.0 mL of Tris-HCl buffer solution (pH = 8.5), stir magnetically at 40 °C for 24 h to fully oxidize and polymerize dopamine into polydopamine (PDA). Filter to remove unreacted monomers to obtain a uniform PDA solution. Preparation of microcapsules: Use a coaxial microfluidic device to prepare microcapsules. The inner tube serves as the core material channel and uses a quartz capillary with an inner diameter of 0.5 mm and an outer diameter of 0.7 mm. The outer tube serves as the wall material channel and uses a stainless steel sleeve with an inner diameter of 1.5 mm and an outer diameter of 2.0 mm. At room temperature, adopt a laminar flow mode, adjust the distance between the inner and outer tubes to 0.4 mm through a precision fixture to ensure stable laminar flow. Control the core material flow rate at 0.2 mL / min (accurately controlled by an injection pump) and the wall material flow rate at 1.0 mL / min. The core material is wrapped by the wall material solution to form monodisperse droplets, and the emulsion is directly collected into a centrifuge tube at the microfluidic outlet. Centrifugal purification: Centrifuge at 3000 rpm for 10 minutes to remove the supernatant (unwrapped core material and free wall material). Washing: Add deionized water (volume: 3 times the volume of the emulsion), and vortex to mix evenly. Repeat the centrifugation (3000 rpm, 5 minutes) and supernatant removal steps 3 times to thoroughly remove impurities. Freeze-drying: Place the washed microcapsule suspension in a -30 °C refrigerator for pre-freezing for 24 hours. Transfer it to a freeze-dryer (-50 °C, 0.1 mbar) for drying for 24 hours to obtain dry microcapsule powder.

[0044] (3) Add 100.0 g of D-WPU emulsion, 8.0 g of microcapsules, and 0.5 g of defoamer, and stir at a low speed (500 rpm, 30 minutes); spray it onto a sandblasted Q235 steel plate (diameter: 30 mm, thickness: 0.5 mm), and pre-cure at room temperature for 24 hours (to volatilize water), and then raise the temperature gradient: cure at 60 °C for 2 hours and at 80 °C for 1 hour.

[0045] Example 4

[0046] A method for preparing a self-repairing waterborne polyurethane coating based on the synergistic effect of dynamic disulfide bonds and pH-responsive microcapsules comprises the following steps: (1) Steel pretreatment: Grind the surface of Q235 plain carbon steel with sandpaper or other tools, then clean the surface with metal cleaning agent, and finally rinse the surface with clean water.

[0047] (2) 100.0 g PTMG (0.05 moL), 44.4 g IPDI (0.2 moL) and 13.3 DMPA (0.1 moL) were added to a three-necked flask, and nitrogen was passed through. The mixture was stirred mechanically at 80 °C for 3 hours to obtain an -NCO-terminated prepolymer. The prepolymer was cooled to 60 °C (cooling rate 5 °C / min), and 12.0 g cystamine hydrochloride (molecular weight 225.7 g / moL) and 0.6 g 1-octanethiol (0.5 wt%) were added. The mixture was stirred under nitrogen for 4 hours, and 200.0 mL deionized water was added for emulsification. Triethylamine was added dropwise to adjust the pH to 7.0 ± 0.5. After filtration, a D-WPU emulsion containing dynamic disulfide bonds (solid content 40%) was obtained.

[0048] (3)Preparation of pH-responsive microcapsules: Preparation of core material solution: Weigh 10.0 g of cysteine, add 90.0 mL of phosphate buffer solution (pH = 4.0), and stir magnetically for 30 min until completely dissolved. Then, ultrasonically disperse it until the solution is clear to avoid particle residue. Preparation of wall material solution: Weigh 1.0 g of dopamine hydrochloride, dissolve it in 99.0 mL of Tris-HCl buffer solution (pH = 8.5), and stir magnetically at 40 °C for 24 h to fully oxidize and polymerize dopamine into polydopamine (PDA). Filter to remove unreacted monomers to obtain a homogeneous PDA solution. Preparation of microcapsules: Use a coaxial microfluidic device to prepare microcapsules. The inner tube serves as the core material channel and uses a quartz capillary with an inner diameter of 0.5 mm and an outer diameter of 0.7 mm. The outer tube serves as the wall material channel and uses a stainless steel sleeve with an inner diameter of 1.5 mm and an outer diameter of 2.0 mm. At room temperature, adopt a laminar flow mode, and adjust the distance between the inner and outer tubes to 0.4 mm through a precision fixture to ensure stable laminar flow. Control the core material flow rate at 0.2 mL / min (precisely controlled by an injection pump) and the wall material flow rate at 1.0 mL / min. The core material is wrapped by the wall material solution to form monodisperse droplets, and the emulsion is directly collected into a centrifuge tube at the microfluidic outlet. Centrifugal purification: Centrifuge at 3000 rpm for 10 minutes to remove the supernatant (unwrapped core material and free wall material). Washing: Add deionized water (3 times the volume of the emulsion), and vortex to mix evenly. Repeat the centrifugation (3000 rpm, 5 minutes) and removing the supernatant steps 3 times to thoroughly remove impurities. Freeze-drying: Place the washed microcapsule suspension in a -30 °C refrigerator for pre-freezing for 24 hours. Transfer it to a freeze-dryer (-50 °C, 0.1 mbar) for drying for 24 hours to obtain dry microcapsule powder.

[0049] (4)Take 100.0 g of D-WPU emulsion, add 8.0 g (8 wt%) of pH-responsive microcapsules, 1.0 g of CNF (1 wt%), and 0.5 g of defoamer, and stir at a low speed (500 rpm, 30 minutes). After mixing, perform ultrasonic treatment to eliminate bubbles; spray it onto a Q235 steel plate (diameter 30 mm, thickness 0.5 mm) treated by sandblasting, and pre-cure it at room temperature for 24 hours (to volatilize moisture), and then gradually increase the temperature: cure at 60 °C for 2 hours and at 80 °C for 1 hour.

[0050] Water absorption test Immerse the steel plates sprayed in Example 2, Example 3, and Example 4 in deionized water. Take them out every 24 hours, dry them with a water-absorbing sponge, record their weights with an electronic balance, and then quickly put them back into the water. Continuously test for 15 days. The water absorption results are shown in Figure 2 ; It can be seen that the addition of the CNF dispersion liquid added in Example 4 effectively increases the mechanical strength of the coating, reduces the water absorption of the coating, and further improves the water resistance of the coating.

[0051] Tensile strength test The coating films of Example 2, Example 3, and Example 4 were peeled off from the steel plates and cut into dumbbell-shaped specimens (length 25 mm × width 4 mm). Before testing, the surface of the samples was wiped with ethanol to remove impurities, and the samples were placed in a standard environment to equilibrate for 48 hours. After recording the original mechanical strength data of the coating, a scratch (depth 50% of the film thickness, length 10 mm) was made in the middle of the sample with a blade. After heating at 60 °C for 1.5 h and standing for 24 hours, the mechanical strength data after self-repair was tested. The test results are as follows: Table 1 Mechanical strength test results of Example 2 Tensile strength (MPa) Elongation at break (%) Elastic modulus (MPa) Original coating 34.4±1.5 288±15 11.3±0.8 Coating after repair 30.7±1.2 261±12 10.6±0.6 Recovery rate 89.2% 90.6% 91.8% Table 2 Mechanical strength test results of Example 3 Tensile strength (MPa) Elongation at break (%) Elastic modulus (MPa) Original coating 35.1±1.5 293±15 11.5±0.8 Coating after repair 31.4±1.2 269±12 10.9±0.6 Recovery rate 89.4% 91.8% 92.7% Table 3 Mechanical strength test results of Example 4 Tensile strength (MPa) Elongation at break (%) Elastic modulus (MPa) Original coating 38.2±1.5 320±15 12.5±0.8 Coating after repair 34.5±1.2 290±12 11.8±0.6 Recovery rate 90.1% 90.6% 91.4% From the above results, it can be seen that for the scratch damage caused by external forces, the self-repair effect is good. In Example 4, a CNF mixture was added, and the CNF was combined with the polyurethane matrix through hydrogen bonds to form a three-dimensional network, which improved the mechanical strength of the coating.

[0052] Macroscopic self-repair temperature test On the steel plates sprayed in Example 2, Example 3, and Example 4, standard scratches (length 20 mm, depth 50% of the coating thickness) were made on the coating surface with a diamond blade. The scratched steel plates were immersed in a buffer solution with a pH value of 3.5. Five temperature points of 40 °C, 50 °C, 60 °C, 70 °C, and 80 °C were selected to cover the dynamic disulfide bond recombination activation energy range and the microcapsule response threshold. The damaged samples were placed in a constant temperature oven and heated to the target temperature respectively, and the holding time was uniformly 1.5 h. The self-repair results are shown in Figure 3 . From Figure 3 it can be seen that in Example 3 and Example 4, the dynamic disulfide bond recombination rate and the microcapsule release behavior reached the best coordination at about 60 °C, and the scratch repair rate > 90%. In Example 2, the best scratch repair rate was achieved at 80 °C, indicating that the addition of cysteine significantly reduced the temperature required for self-repair.

[0053] Salt spray test Verify the long-term anti-corrosion performance of the self-healing coating in a salt spray environment and evaluate the inhibitory effect of its self-healing mechanism on corrosion diffusion. For the experimental group, the self-healing coating sample prepared in Example 4 (containing dynamic disulfide bonds, pH-responsive microcapsules and CNF) was sprayed on a Q235 steel plate (100 mm × 50 mm × 1 mm). Artificial scratches (20 mm in length and 50% of the coating thickness in depth) were made on the coating surface and then repaired by heating at 60 °C for 1.5 h for standby. For the control group, the self-healing coating sample prepared in Example 2 was sprayed on a Q235 steel plate (100 mm × 50 mm × 1 mm). Artificial scratches (20 mm in length and 50% of the coating thickness in depth) were made on the coating surface and then repaired by heating at 60 °C for 1.5 h for standby. The samples of the experimental group and the control group were vertically suspended in the salt spray chamber with a spacing of ≥20 mm. A 5% NaCl solution (35 ± 2 °C) was continuously sprayed, and the test period was 720 hours. The test was paused every 24 hours, and the samples were taken out to observe and record the corrosion situation in the scratched area. The test results are as follows: Table 4 Salt spray test results Test index Experimental group Control group Corrosion expansion width after 240 hours ≤0.2mm ≥1.5mm Rust grade after 480 hours Slight rust spots, area < 5% Obvious rust patches, area > 30% Adhesion after 720 hours 5B 0B Proportion of corrosion area ≤3% ≥50% From the above results, it can be seen that a passivation film was formed in the scratched area of the experimental group due to the release of cysteine. After 720 hours of salt spray exposure, the corrosion area was only 3%, while that of the control group reached 50%. This shows that cysteine, as a natural and environmentally friendly passivating agent, its mercapto group can reduce the oxide layer on the metal surface; the amino group of cysteine can form an ionic bond with the carboxyl group of the polyurethane matrix, enhancing the cohesion of the coating, increasing the tensile strength and enhancing the adhesion of the coating.

[0054] The above content is a further detailed description of the present invention in combination with specific preferred embodiments. It cannot be determined that the specific implementation of the present invention is only limited to these descriptions. For those of ordinary skill in the technical field to which the present invention belongs, without departing from the concept of the present invention, several simple deductions or substitutions can still be made, which should all be regarded as belonging to the protection scope of the present invention.

Claims

1. A preparation method of a self - healing aqueous polyurethane coating based on the synergistic effect of dynamic disulfide bonds and pH - responsive microcapsules, characterized in that It includes the following steps: Step 1: Prepare an aqueous polyurethane (D-WPU) emulsion containing dynamic disulfide bonds; Step 2: Prepare pH-responsive microcapsules; Step 3: Prepare a self-healing aqueous polyurethane coating.

2. The preparation method of a self-healing aqueous polyurethane coating based on the synergistic effect of dynamic disulfide bonds and pH-responsive microcapsules as claimed in claim 1, wherein: The specific process of the said Step 1: Prepare an aqueous polyurethane (D-WPU) emulsion containing dynamic disulfide bonds is as follows: Mix polytetrahydrofuran diol (PTMG, Mn = 2000), isophorone diisocyanate (IPDI), and 2,2-dimethylolpropionic acid (DMPA, carboxyl content 5%) in a ratio of the molar ratio of NCO groups to hydroxyl groups (OH) of 2:1, react at 80 °C for 3 hours to obtain an NCO-group-terminated prepolymer. Cool the prepolymer to 60 °C, add cystamine hydrochloride (—NCO:NH2 = 1:0.6) and a thiol catalyst, react for 4 hours under nitrogen protection, add deionized water for emulsification (solid content 40%), and adjust the pH to 7.0 ± 0.5 to obtain a D-WPU emulsion containing dynamic disulfide bonds.

3. The preparation method of a self-healing aqueous polyurethane coating based on the synergistic effect of dynamic disulfide bonds and pH-responsive microcapsules as claimed in claim 1, wherein: The specific steps of the said Step 2: Prepare pH-responsive microcapsules are as follows: Step 201: Preparation of core material solution: Weigh 10.0 g of cysteine, add 90.0 mL of phosphate buffer solution (pH = 4.0), stir magnetically for 30 min until completely dissolved, and ultrasonically disperse until the solution is clear to avoid particle residues; Step 202: Preparation of wall material solution: Weigh 1.0 g of dopamine hydrochloride, dissolve it in 99.0 mL of Tris-HCl buffer solution (pH = 8.5), stir magnetically at 40 °C for 24 h to fully oxidize and polymerize dopamine into polydopamine (PDA), filter to remove unreacted monomers, and obtain a homogeneous PDA solution; Step 203: Preparation of microcapsules: Use a coaxial microfluidic device to prepare microcapsules, control the flow rate ratio of the core material to the wall material solution to be 1:5, and directly collect the emulsion at the microfluidic outlet into a centrifuge tube to form monodisperse microcapsules; Step 204: Centrifugal purification: Centrifugal speed: 3000 rpm, time: 10 minutes; Remove the supernatant; Step 205: Washing: Add deionized water and vortex to mix evenly; repeat centrifugation (3000 rpm, 5 minutes) and the step of removing the supernatant 3 times to completely remove impurities; Step 206: Freeze-drying: Pre-freezing: Place the washed microcapsule suspension in a -30 °C refrigerator and freeze for 24 hours; Drying: Transfer to a freeze dryer (-50 °C, 0.1 mbar) and dry for 24 hours to obtain dry microcapsule powder.

4. The preparation method of a self-healing aqueous polyurethane coating based on the synergistic effect of dynamic disulfide bonds and pH-responsive microcapsules according to claim 3, characterized in that: The inner tube of the said coaxial microfluidic device is used as the core material channel and is a quartz capillary with an inner diameter of 0.5 mm and an outer diameter of 0.7 mm. The outer tube is used as the wall material channel and is a stainless steel sleeve with an inner diameter of 1.5 mm and an outer diameter of 2.0 mm. The distance between the inner and outer tubes is adjusted to 0.4 mm through a precision fixture, and the core material flow rate is controlled at 0.2 mL / min, and the wall material flow rate is 1.0 mL / min.

5. The preparation method of a self-healing aqueous polyurethane coating based on the synergistic effect of dynamic disulfide bonds and pH-responsive microcapsules as claimed in claim 1, wherein: The specific process of the said Step 3: Prepare a self-healing aqueous polyurethane coating is as follows: The D-WPU emulsion, microcapsules (8 wt%), TEMPO-oxidized nanocellulose (CNF, 1 wt%), and defoamer (0.5 wt%) were stirred at a low speed (500 rpm, 30 minutes); then sprayed onto the pretreated Q235 steel plate and pre-cured at room temperature for 24 hours, followed by a gradient temperature increase: cured at 60 °C for 2 hours and at 80 °C for 1 hour.

6. The preparation method of a self-healing aqueous polyurethane coating based on the synergistic effect of dynamic disulfide bonds and pH-responsive microcapsules as claimed in claim 5, wherein: The pretreatment process of the Q235 steel plate is as follows: the surface of the Q235 carbon steel plate was polished with sandpaper, then its surface was cleaned with a metal cleaning agent, and finally the surface was rinsed clean with water.

7. The preparation method of a self-healing aqueous polyurethane coating based on the synergistic effect of dynamic disulfide bonds and pH-responsive microcapsules according to claim 2, characterized in that: The mercaptan catalyst is 1-octanethiol, and the addition amount is 0.5 wt% of the total mass of the prepolymer.

8. The preparation method of a self-healing aqueous polyurethane coating based on the synergistic effect of dynamic disulfide bonds and pH-responsive microcapsules as claimed in claim 1, wherein: The self-healing waterborne polyurethane coating can achieve scratch repair when heated at 50-60 °C for 1-1.5 h, and the mechanical strength recovery rate is ≥90%.

9. The preparation method of a self-healing aqueous polyurethane coating based on the synergistic effect of dynamic disulfide bonds and pH-responsive microcapsules as claimed in claim 1, characterized in that: The polydopamine shell of the pH-responsive microcapsules degrades at pH < 4.0, releasing cysteine. Its sulfhydryl group (-SH) catalyzes the recombination of dynamic disulfide bonds, and after the amino group (-NH2) is protonated, an ionic bond is formed with the carboxyl group of the polyurethane, enhancing the mechanical strength of the self-healing waterborne polyurethane coating.

Citation Information

Cited By

  • Modified degradable fiber and preparation method thereof

    CN121023668A

  • Degradable glove for ocean engineering and preparation method thereof

    CN121592157A

  • Self-repairing weather-resistant heat-conducting paint and preparation method thereof

    CN122521223A